The EU Green Deal and its industrial and political significance - Hosuk Lee-Makiyama (European Centre for International Political Economy (ECIPE), 2021)
The European Green Deal, the flagship initiative of the incumbent European Commission, aims to cut greenhouse gas (GHG) emissions to 55% by 2030 (from the current target of cutting 40% of 1990 levels) by overhauling fiscal, trading and regulatory regimes. Brussels is well-placed to deliver the interregional distribution or the minutiae of technical regulations that this challenge calls for. Energy diversification is also central to EU competitiveness and strategic autonomy. But this initiative is not costless: its official impact assessment points to a GDP loss of additional -0.3 to -0.7%, by 2030, relative to the previous level of ambition. The full loss could be up to -2.5%. These costs are also unevenly, and the inability to cushion asymmetrical shocks have nearly torn the Union apart in the past. A carbon-neutral Europe could also make losers out of today's winners among stakeholders and give the EU a significantly different industrial structure, forcing over-exporting Northern Europe into reforms that are probably overdue. Most importantly, the gap between the financing needed and the financing available is unprecedented. The success of the European Green Deal and a cost-efficient transition hinge on the rapid and effective mobilisation of investments - as the diffusion period for new energy-related technology is 40-50 years. Therefore, a smart climate policy does not just distribute costs and investments between different groups, but also over time: The investments are needed now, if we are to reap their benefits before 2050.
Keywords: 330; EU-Umweltpolitik; EU-Umweltrecht; Treibhausgas-Emissionen; EU-Energiepolitik; Förderung erneuerbarer Energien